High-intensity intermittent exercise performed on the sand induces higher internal load demands in soccer players - Cetolin, T.; Teixeira, A. S.; da Silva, J. F.; Haupenthal, A.; Nakamura, F. Y.; Castagna, C.; Guglielmo, L. G. A. (Frontiers in Psychology, 2021)
This study aimed to examine the acute physiological effect of shuttle-run-based high-intensity intermittent exercise (HIIE) performed at the same relative speed (i. e., 100% PST-CAR) on sand (SAND) and grass (GRASS) in male junior soccer players. Seven Under-23 Brazilian national league ("Série A") soccer players completed four testing sessions in either SAND or GRASS surface condition. The first two testing sessions consisted of performing a maximal progressive shuttle-run field protocol until volitional exhaustion (Carminatti's test, T-CAR), whereas the third and fourth sessions comprised a HIIE session on each ground surface. The HIIE session consisted of three 5-min bouts [12 s shuttle-run (with a direction change every 6 s)/12 s of passive rest] performed at 100% of T-CAR peak speed (PST-CAR) with 3 min of passive recovery between sets. Measurements of oxygen uptake (VO2), heart rate (HR), blood lactate concentration ([La]), and rating of perceived exertion (RPE) were performed during all conditions. The SAND condition elicited significantly higher %VO2peak (94.58 ± 2.73 vs. 87.45 ± 3.31%, p < 0.001, d = 2.35), %HRpeak (93.89 ± 2.63 vs. 90.31 ± 2.87%, p < 0.001, d = 1.30), RPE (8.00 ± 0.91 vs. 4.95 ± 1.23 a.u., p < 0.001, d = 2.82), and [La] (10.76 ± 2.37 vs. 5.48 ± 1.13 mmol/L, p < 0.010, d = 2.84). This study showed that higher internal workloads are experienced by the players during a single HIIE session performed on a softer surface as SAND, even when the exercise intensity was individualized based on 100%PST-CAR.